2020
DOI: 10.1111/epi.16731
|View full text |Cite
|
Sign up to set email alerts
|

Seven‐tesla quantitative magnetic resonance spectroscopy of glutamate, γ‐aminobutyric acid, and glutathione in the posterior cingulate cortex/precuneus in patients with epilepsy

Abstract: Objective: The posterior cingulate cortex (PCC)/precuneus is a key hub of the default mode network, whose function is known to be altered in epilepsy. Glutamate and γ-aminobutyric acid (GABA) are the main excitatory and inhibitory neurotransmitters in the central nervous system, respectively. Glutathione (GSH) is the most important free radical scavenging compound in the brain. Quantification of these molecules by magnetic resonance spectroscopy (MRS) up to 4 T is limited by overlapping resonances from other m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…Similarly, a more recent study on 7 T MRS demonstrated increased levels of glutathione in the posterior cingulate cortex (PCC)/precuneus of patients with idiopathic generalized epilepsy compared with the healthy volunteers (2.2 ± 0.4 compared with 2.0 ± 0.2 mM/L, respectively); this controversial finding suggested increased GSH levels as an early response to oxidative stress. No difference was found in the levels of other metabolites such as GABA and glutamate [ 7 ].…”
Section: Clinical Applications Of Gsh Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a more recent study on 7 T MRS demonstrated increased levels of glutathione in the posterior cingulate cortex (PCC)/precuneus of patients with idiopathic generalized epilepsy compared with the healthy volunteers (2.2 ± 0.4 compared with 2.0 ± 0.2 mM/L, respectively); this controversial finding suggested increased GSH levels as an early response to oxidative stress. No difference was found in the levels of other metabolites such as GABA and glutamate [ 7 ].…”
Section: Clinical Applications Of Gsh Imagingmentioning
confidence: 99%
“…Changes in the GSH brain concentration from oxidative stress may reflect inflammatory processes and mitochondrial dysfunction associated with biological aging [ 3 ] and pathological conditions [ 4 , 5 ]. In particular, as high levels of ROS may lead to cerebral tissue damage, the altered GSH concentration of specific brain areas has been described in several neurologic disorders, including epilepsy [ 6 , 7 ], multiple sclerosis [ 8 , 9 ], Alzheimer’s disease [ 10 ], Parkinson’s disease [ 11 , 12 ], and psychiatric disorders [ 13 , 14 , 15 , 16 ]. In order to provide a clear and thorough understating of GSH metabolism within the brain, an accurate and reliable estimation of cerebral concentrations needs to be performed.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have used phantom data to provide evidence that it is possible to measure changes in GSH concentration using 1 H-MRS, and GSH can be quantified reproducibly in vivo ( 28 , 29 ). GSH has been measured by 1 H-MRS in humans in a number of neurological diseases such as Alzheimer's disease ( 30 ), schizophrenia ( 31 ), and epilepsy ( 32 ). To our knowledge, this study was the first to investigate the changes in brain GSH in migraineurs using 1 H-MRS. GSH is the major cellular antioxidant that is essential for cellular function, plays roles in oxidation–reduction reactions, and protects against reactive oxygen species ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione has been successfully imaged and quantified using 3T MRS techniques, though images obtained at this field strength may lack the fidelity and accuracy for detecting small changes in clinical trials [ 85 ]. Along with the 3T imaging glutathione, 7T MRS imaging can also assess glutathione as well [ 98 ]. Ultra-high MRI uses 7T scanners that are primarily used for research on human subjects, but it has not been used regularly in clinical studies.…”
Section: Tracking Frda With Mitochondrial Biomarkers and Imagingmentioning
confidence: 99%
“…Ultra-high MRI uses 7T scanners that are primarily used for research on human subjects, but it has not been used regularly in clinical studies. 7T images can be heavily affected by the smallest movements; in some cases, subjects’ heartbeats could move the brain by under a millimeter, altering the results [ 98 ]. Its safety in children is also unknown.…”
Section: Tracking Frda With Mitochondrial Biomarkers and Imagingmentioning
confidence: 99%